Inland barge services and container transport: the case of the ports of Le Havre and Marseille in the European context - Antoine Frémont; Pierre Franc; Brian Slack (Cybergeo, 2009)
Ports that are able to offer scale economies on land by using combined transport gain a competitive advantage in their port range. The recent rapid expansion of combined waterway-road services at French ports, Le Havre and Marseille, led us to carry out a theoretical and empirical analysis of the causes and conditions that underline this development. In order to more clearly understand the dynamics of the French situation, attention has been broadened to include other competing European ports, Antwerp and Rotterdam. The four-stage theoretical model highlights the interdependence between the setting up of combined waterway-road services, the competition between ports and the competition between shipping lines.